Optimizing intravenous fosfomycin dosing in combination with carbapenems for treatment of Pseudomonas aeruginosa infections in critically ill patients based on pharmacokinetic/pharmacodynamic (PK/PD) simulation. (September 2016) - Asuphon, O.; Montakantikul, P.; Houngsaitong, J.; Kiratisin, P.; Sonthisombat, P.
Highlights: MICs90 of fosfomycin for MDR PA and non MDR PA were high in this study. Approximately 40% of the non-MDR PA was carbapenem-resistant strains. The combination of fosfomycin and carbapenems decreased the MICs of both drugs. Prolonged infusion of fosfomycin combination provided the best PK/PD targets. Abstract: Objective: The purpose of the study was to determine the optimal dosing regimen of intravenous fosfomycin for the treatment of Pseudomonas aeruginosa ( PA ) based on PK/PD targets. Method: A total of 120 PA isolates were recovered from various clinical specimens at university hospital in Thailand. Minimum Inhibitory Concentrations (MICs) of all the isolates were determined by the E-test method. PK parameters were obtained from a published study. Monte Carlo simulation was performed to calculate the percentage of target attainment (PTA) and cumulative fraction of response (CFR). Results: MIC90 of fosfomycin alone, fosfomycin in combination with carbapenem, carbapenems alone and carbapenems in combination with fosfomycin were >1, 024, 1, 024, >32 and 32 μg/ml, for multidrug resistant (MDR)-PA and 512, 128, 8 and 3 μg/ml respectively, for non-MDR PA. Approximately 40% of the non-MDR PA were carbapenem-resistant strains. For non-MDR PA with CRPA, fosfomycin 16 g continuous infusion in combination with carbapenems provided %PTA of approximately 80 and %CFR of > 88. While, %PTA and %CFR > 90 were achieved with fosfomycin 24 g/day prolonged infusion in combination with carbapenem. Conclusions: Prolonged infusion of fosfomycin 16 - 24 g combined with extended carbapenem infusion could be used in non-MDR PA treatment with CRPA.